Building User Centered On-line Help - Sellen, Abigail; Nicol, A. (B. Laurel (Ed.),The art of human-computer interface design, 1990)
This chapter discusses the design process for building user-centered on-line help. On-line help can be interactive and action-dependent. It can be dependent on the user's working context or on the history of a user's actions, and can take account of a user's skill level. On-line help can also be dynamic. Instead of having users read pages of printed text, help information can be presented using animation, even with voice overlay. Other features that can be incorporated into on-line help are the ability to do keyword searches, and the ability to cut information directly out of the help text and paste it into the working environment. This chapter discusses major issues that arise in the design of help systems to address user needs and complaint. It describes the research approach taken, some results of that research, and some of prototype solutions and guidelines, and also examines future directions for on-line help.